Obras de arte da exposição Queermuseu (2017) em polêmica: composição axiológica e conflito entre defensores da liberdade artística e político-religiosos - Lopes, Priscila Santos (2025)
Contemporary art in Brazil has been the setting for several peaceful and conflicting debates about its function in the public space. In the recent past, specifically in 2017, yet another exhibition generated controversial opinions. In this context, defenders of artistic freedom and politico-religious leaders led discussions about the meaning of artistic productions. Motivated by basing their concept of art on different bases, these antagonistic groups expressed profoundly dissonant points of view about some artistic productions, especially the work of the artist Bia Leite "Travesti da lambada e deusa das águas" (2013), which constitutes the series "Born to Ahazar", exhibited in the exhibition Queermuseu – Cartographies of Difference in Brazilian Art. held in Porto Alegre, Rio Grande do Sul. Thus, in this dissertation, the objective was to present the characterization of the deep disagreement between the parties involved. In addition, it was intended to understand not only how the controversial event around the aforementioned issue took place, but also how the groups imprinted in their speechescultural and political aspects that reflect the contemporaneity in digital media. The study is based on the perspective of the Dialogic Analysis of Argumentation, proposed by Lucas Nascimento (2018), based on Mikhail Bakhtin (2010; 2011; 2013; 2017; 2020) and Chaїm Perelman and Lucie Olbrechts-Tyteca (2014 [1966]), in dialogue with Ruth Amossy (2017) and Marc Angenot (2008). In addition, the contributions of Digital Discourse Analysis (Paveau, 2013a, Paveau, 2013b; Paveau, 2013c; Paveau, 2021), regarding the characterization of opinion articles, editorial and Multimodal Argumentation (Kjeldsen, 2015;2018, Tseronis, 2018; Gonçalves-Segundo, 2021; 2022), to understand the role of verbal-imagery interaction in the polemic event. From these perspectives, it was possible to analyze the disagreement in the opinion articles published in the online newspapers, in which the arguments of the opponents sound irrational and unacceptable to the arguing artists. The results showed that the controversial event analyzed took place because the discursive fields in dispute differed on issues related to values, and not because there was stylistic incoherence in the works of art. For this reason, the work Travesti da lambada e deus das águas was one of the most discussed. In addition, the analysis of the corpora, made up of seven opinion articles and one editorial, whose authors are argumentative subjects positioned in different political spectrums, confirmed the emphasis on values.